2010
DOI: 10.3109/02770903.2010.506682
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the asthmatic population of St. Vincent and the Grenadines: Asthma severity levels and atopic sensitization

Abstract: The predominance of asthma with atopy in SVG implicates a role for atopy in the sudden rise in asthma cases. This asthma characteristic and the increase in persistent asthma with age in SVG are similar to those reported in the developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The most frequently reported triggers of asthma exacerbations of house dust and the common cold/ virus are supported by an earlier report in Trinidadian children (18) and elsewhere (28,29). In the nearby island country of St Vincent and the Grenadines, the house dust mite was identified as the most common allergen in 93.4% of 121 atopic children (30). Trinidad, regarded as the gateway to the Caribbean, has in the past decade seen an unprecedented increase in commercial and industrial expansion (31), with considerable construction activity so that environmental dust should also be investigated as an important risk factor for childhood wheeze.…”
Section: Discussionsupporting
confidence: 56%
“…The most frequently reported triggers of asthma exacerbations of house dust and the common cold/ virus are supported by an earlier report in Trinidadian children (18) and elsewhere (28,29). In the nearby island country of St Vincent and the Grenadines, the house dust mite was identified as the most common allergen in 93.4% of 121 atopic children (30). Trinidad, regarded as the gateway to the Caribbean, has in the past decade seen an unprecedented increase in commercial and industrial expansion (31), with considerable construction activity so that environmental dust should also be investigated as an important risk factor for childhood wheeze.…”
Section: Discussionsupporting
confidence: 56%
“…The HELIUS study examining six ethnic groups in the Netherlands (Dutch, South-Asian Surinamese, African Surinamese, Moroccan, and Turkish and Ghanaian origin) and evaluating 23,356 participants, demonstrated a prevalence of LOA (age cut-off ≥18 years) ranging from 2.4% to 6.0% in these populations. 28 A Swedish population-based study in 15,813 adults revealed that the incidence rate of LOA 12 Miranda (2004) 8 Holguin et al (2011) 13 Bhaskar et al (2013) 14 16 years Toren et al (1999) 15 Jarvis et al (2012) 16 18 years Sood et al (2013) 17 Chaudhuri et al (2016) 18 Schwindt et al (2010) 19 20 years Bedolla-Barajas et al (2015) 20 30 years Nenasheva et al (2019) 30 40 years Maio et al (2018) 21 Heffler et al (2019) 22 13-50 years Wu et al (2015) 23 64/65 years Bauer et al (1997) 24 Gillman et al (2012) 25 Ariano et al (2012) 26 Gibson et al (2010) 27 submit your manuscript | www.dovepress.com…”
Section: Epidemiology Of Loamentioning
confidence: 99%
“…As discussed in previous reviews [3,4], these original observations explain only part of the story. Several recent articles highlight the increasing prevalence of asthma/ atopy in developing nations, despite little change in the infectious agents afflicting children [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%